Prevalence of palb2 germline mutations in malaysian breast cancer patients and its role in predisposition to breast cancer / Phuah Sze Yee - Phuah, Sze Yee (2014)
The PALB2 (Partner and Localizer of BRCA2) protein stabilizes and localizes the BRCA2 protein at nuclear foci in response to DNA damage. Biallelic PALB2 variants cause Fanconi anemia, a recessive inherited chromosomal instability syndrome, while rare monoallelic variants of PALB2 have been proposed to confer two-fold increased predisposition to breast cancer. To investigate the role of PALB2 germline mutations in predisposition to breast cancer in the Malaysian breast cancer patient population and to determine its clinical significance, a total of 1220 breast cancer patients treated at University Malaya Medical Centre (UMMC) from January 2003 to December 2010 were recruited into the Malaysia Breast Cancer Genetic Study (MyBrCa). We selected 155 high risk individuals with either (a) diagnosed ≤50 years old and had at least one first- or second-degree relatives with breast cancer; (b) diagnosed with bilateral breast cancer with the primary cancer at age 50 or below; (c) diagnosed with male breast cancer at any age; (d) affected with both breast and ovarian cancers; (e) affected with both breast and pancreatic cancers; or (f) diagnosed with breast cancer and had at least one first-degree relative with pancreatic cancer. Of these, 33 individuals were screened positive for BRCA deleterious mutations, while 122 individuals lacked aberrations in both BRCA1 and BRCA2 genes. These 122 BRCA-negative individuals were then tested for PALB2 germline mutations. Further screening for nine PALB2 mutations/variants was conducted in 874 Malaysian and 532 Singaporean breast cancer patients, and in 1342 healthy Malaysian and 541 healthy Singaporean women. In-silico prediction of the pathogenicity of missense variants were conducted using both SIFT and Polyphen-2. Statistical analyses were performed to compare the characteristics of PALB2 mutation carrier relative to BRCA1, BRCA2 and non-carrier. We discovered two PALB2 deleterious mutations (STOP358 and S869X), ten missense variants (P249L, T300I, iv I309V, E352Q, D498Y, H553Q, Q559R, L763F, A1017T and E1018D) and one synonymous variant (S689S) from the sequencing of 122 BRCA-negative individuals. Genotyping of Asian recurrent PALB2 mutations detected an additional PALB2 carrier (STOP353) among the unselected breast cancer patients. Variants classification using both case-control study and in-silico predictions enabled the characterization of PALB2 P249L, I309V, E352Q, D498Y and Q559R to be possibly benign while PALB2 H553Q, T300I, L763F, A1017T and E1018D remain as unclassified variants. Kruskal Wallis and Mann-Whitney analyses showed that the presence of PALB2 mutations was not significantly associated with higher incidence of breast or BRCA-related cancers. Germline pathogenic PALB2 mutations were found in 1.6% (2 out of 122) of high risk BRCA-negative individuals. The low prevalence of breast cancers among PALB2 carrier families suggests that PALB2 may be a moderate penetrance breast cancer susceptibility gene in the Malaysian breast cancer population.